China and ASEAN energy security, cooperation and competition - Zhao, Hong (ISEAS Yusof Ishak Institute, 2015)
Examines the energy resource relations between China and ASEAN countries. It explores whether geopolitical tensions over energy resources will spark conflicts in the region, especially in the South China Sea; and asks ifChina's quest for energy resource cooperation should be viewed as a threat or opportunity by its neighbouring countries.